IMPLEMENTASI PERATURAN LEMBAGA ADMINISTRASI NEGARA REPUBLIK INDONESIA NOMOR 16 TAHUN 2019 TENTANG PELATIHAN KEPEMIMPINAN ADMINISTRATOR DALAM PENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA DI KOTA BONTANG - Kristiana, Diesta (Jurnal Administrative Reform, 2023)
Diesta Kristiana, Mulawarman University Master of Public Administration Postgraduate Program, July 2023, Implementation of Republic of Indonesia State Administration Agency Regulation Number 16 of 2019 Concerning Administrator Leadership Training in Developing State Civil Apparatus Competence in Bontang City, supervised by Prof. Dr. H. Adam Idris, M.Sc. as Advisor I and Dr. H.M. Jamal Amin, M.Si as Advisor II. With the examiners, Mrs.Prof. Dr. Hj Aji Ratna Kusuma, M.Si, as Examiner Lecturer I, Mr. Dr. Heryono Susilo Utomo, M.Si,, as Examiner II, and Mr. Dr. Kus Indarto, MAP as Examiner III.The aim of this study is to explain the Implementation of the Republic of Indonesia State Administration Agency Regulation Number 16 of 2019 Concerning Administrator Leadership Training in the Development of State Civil Apparatus (ASN) Competence in Bontang City and identify the inhibiting factors in the Implementation of the Republic of Indonesia State Administration Institution Regulation Number 16 of 2019 Concerning Administrator Leadership Training in Bontang City.The results of the study show that the implementation of the Republic of Indonesia State Administrative Institution Regulation Number 16 of 2019 concerning Administrator Leadership Training in Developing State Civil Apparatus (ASN) Competence in Bontang City was carried out properly by the Bontang City BKPSDM and the Samarinda KDOD LAN Puslatbang through 4 (four) agendas PKA learning, namely the Pancasila leadership agenda and nationalism; Performance leadership agenda; performance management agenda; and the leadership actualization agenda from 2019 until now, although it was held based on the health protocol in 2020 and 2021 which was carried out online or online (on the network), then since 2022 it has been carried out using 2 (two) approaches, namely e-learning or online and face-to-face classics..The success of the implementation is supported by excellent human resources, from the internal BKPSDM of Bontang City and the Samarinda KDOD LAN Samarinda Research and Development Center, as well as the support of non-HR resources such as infrastructure, facilities and regulations which are quite complete. Even so, there are a number of inhibiting factors that need to be minimized, namely the presence of participants who have exceeded the maximum regulatory limit, limited local government budgets, and unstable weather which can cause network or internet signal disturbances.Diesta Kristiana, Mulawarman University Master of Public Administration Postgraduate Program, July 2023, Implementation of Republic of Indonesia State Administration Agency Regulation Number 16 of 2019 Concerning Administrator Leadership Training in Developing State Civil Apparatus Competence in Bontang City, supervised by Prof. Dr. H. Adam Idris, M.Sc. as Advisor I and Dr. H.M. Jamal Amin, M.Si as Advisor II. With the examiners, Mrs.Prof. Dr. Hj Aji Ratna Kusuma, M.Si, as Examiner Lecturer I, Mr. Dr. Heryono Susilo Utomo, M.Si,, as Examiner II, and Mr. Dr. Kus Indarto, MAP as Examiner III.The aim of this study is to explain the Implementation of the Republic of Indonesia State Administration Agency Regulation Number 16 of 2019 Concerning Administrator Leadership Training in the Development of State Civil Apparatus (ASN) Competence in Bontang City and identify the inhibiting factors in the Implementation of the Republic of Indonesia State Administration Institution Regulation Number 16 of 2019 Concerning Administrator Leadership Training in Bontang City.The results of the study show that the implementation of the Republic of Indonesia State Administrative Institution Regulation Number 16 of 2019 concerning Administrator Leadership Training in Developing State Civil Apparatus (ASN) Competence in Bontang City was carried out properly by the Bontang City BKPSDM and the Samarinda KDOD LAN Puslatbang through 4 (four) agendas PKA learning, namely the Pancasila leadership agenda and nationalism; Performance leadership agenda; performance management agenda; and the leadership actualization agenda from 2019 until now, although it was held based on the health protocol in 2020 and 2021 which was carried out online or online (on the network), then since 2022 it has been carried out using 2 (two) approaches, namely e-learning or online and face-to-face classics..The success of the implementation is supported by excellent human resources, from the internal BKPSDM of Bontang City and the Samarinda KDOD LAN Samarinda Research and Development Center, as well as the support of non-HR resources such as infrastructure, facilities and regulations which are quite complete. Even so, there are a number of inhibiting factors that need to be minimized, namely the presence of participants who have exceeded the maximum regulatory limit, limited local government budgets, and unstable weather which can cause network or internet signal disturbances.